2018
DOI: 10.1097/qai.0000000000001673
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Reduction Among African American Women With HIV: UNITY Health Study

Abstract: Although UNITY did not significantly reduce HIV-related stigma in this population, our findings suggest that social support may be key to HIV-related stigma reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…We conducted a secondary analysis of longitudinal data from participants in the Unity Health Study (Rao, Kemp, et al, 2018), a randomized controlled trial that tested the effectiveness of a peer-led HIV-related stigma reduction intervention among 239 AA WLWH. Of those, 237 had at least one HIV medical care appointment scheduled during the study period and were included in our secondary analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted a secondary analysis of longitudinal data from participants in the Unity Health Study (Rao, Kemp, et al, 2018), a randomized controlled trial that tested the effectiveness of a peer-led HIV-related stigma reduction intervention among 239 AA WLWH. Of those, 237 had at least one HIV medical care appointment scheduled during the study period and were included in our secondary analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The Unity Health Study was approved by the institutional review boards at each of the participating study sites, and each study participant provided written informed consent prior to participating in study activities. Comprehensive details of the Unity Health Study are reported in Rao, Kemp, et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a secondary analysis of baseline data from the Unity Study, a multisite randomized controlled trial evaluating the longterm effectiveness of an HIV-related stigmareduction intervention for African-American women living with HIV. 56 From 2013 to 2015, African-American women living with HIV were recruited from three clinical sites that provide HIV care: Northwestern University Infectious Diseases HIV clinic (NU) and the Ruth M. Rothstein CORE Center (CORE) in Chicago, Ilinois and the University of Alabama, Birmingham 1917 HIV Clinic (UAB) in Birmingham, Alabama.…”
Section: Data Sourcementioning
confidence: 99%
“…While some clinic-based strategies such as early initiation of ART have improved retention in care (Brown et al., 2016 ), other clinic-based strategies such as peer support or innovative counselling programmes have lacked anti-stigma or health outcome benefits, respectively (Rao et al., 2018 ; Uusküla et al., 2018 ). Some HIV-infected persons who take ART face barriers to care and require accompaniment in the community for various reasons, ranging from a weak health system, stigma, social ostracisation, alcohol abuse, as well as competing demands on time and money in the context of widespread abject poverty (Fatti, Meintjes, Shea, Eley, & Grimwood, 2012 ; Munyaneza et al., 2018 ; Pokhrel, Gaulee Pokhrel, Neupane, & Sharma, 2018 ; Vogt et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%